Language, religion and national identity in Europe and the Middle East : a historical study - Myhill, John, 1956- (Amsterdam ; Philadelphia : J. Benjamins, 2006)
This book discusses the historical record of the idea that language is associated with national identity, demonstrating that different applications of this idea have consistently produced certain types of results. Nationalist movements aimed at 'unification', based upon languages which vary greatly at the spoken level, e.g. German, Italian, Pan-Turkish and Arabic, have been associated with aggression, fascism and genocide, while those based upon relatively homogeneous spoken languages, e.g. Czech, Norwegian and Ukrainian, have resulted in national liberation and international stability. It is.
Language, Religion and National Identity in Europe and the Middle East; Editorial page; Title page; LCC data; Table of contents; Acknowledgements; Dedication page; Introduction; Premodern national churches, Roman Europe, and the Caliphate; Small languages and national liberation; Big languages, delusions of grandeur, war, and fascism; Language, religion, and nationalism in Europe; Language, religion, and nationalism in the Middle East; Conclusion; Bibliography; Index; The series Discourse Approaches to Politics, Society and Culture.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 082
Keywords: Nationalism -- Europe -- History; Nationalism -- Middle East -- History; Language and languages -- Religious aspects -- Christianity; Language and languages -- Religious aspects -- Islam; Europe -- Languages -- Political aspects; Middle East -- Languages -- Political aspects; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Sociolinguistics; Language and languages -- Political aspects; Language and languages -- Religious aspects -- Christianity; Language and languages -- Religious aspects -- Islam; Nationalism; Europe; Middle East; Electronic books; History